Адміністративно-правові засади протидії торгівлі жінками : дисертація - Черненко, В. В.; Chernenko, V. V. (Харківський національний університет внутрішніх справ, 2023)
Дисертаційну роботу присвячено визначенню сутності та особливостей адміністративно-правових засад протидії торгівлі жінками, а також розробленню пропозицій та рекомендацій, спрямованих на вдосконалення адміністративного законодавства у відповідній сфері.

The thesis has been devoted to defining the essence and features of the administrative and legal framework for combating trafficking in women, as well as developing proposals and recommendations aimed at improving administrative legislation in the relevant area. The methodological foundations of combating trafficking in women are defined. The theoretical and legal prerequisites for the emergence of the problem of combating trafficking in women are determined. The global trends in the formation and development of legislation in the field of combating trafficking in women are identified. The legal framework for combating trafficking in women is described and the place of administrative and legal regulation among them is determined. The administrative and legal mechanism for combating trafficking in women is characterised. The principles of administrative and legal regulation of combating trafficking in women are outlined. The system of subjects of combating trafficking in women is described, and the peculiarities of their administrative and legal status are revealed. The tasks and functions of the subjects of combating trafficking in women are established. The administrative and legal forms and methods of combating trafficking in women are revealed. Directions for improving the administrative and legal framework for combating trafficking in women are identified. The foreign experience of combating trafficking in women is summarised and the possibilities of its use in Ukraine are explored. Ways to improve interaction and coordination between actors involved in combating trafficking in women are identified. Promising areas for improving administrative legislation regulating combating trafficking in women are outlined.

Диссертационная работа посвящена определению сущности и особенностей административно-правовых основ противодействия торговле женщинами, а также разработке предложений и рекомендаций, направленных на усовершенствование административного законодательства в соответствующей сфере.
Administrative and legal principles of combating trafficking in women
Keywords: Україна; 12.00.07; 081 – Право; Дисертації. Theses. Диссертации; торгівля жінками; протидія торгівлі людьми; адміністративно-правове регулювання; адміністративне законодавство; trafficking in women; counteraction; administrative and legal regulation; administrative and legal forms; administrative legislation; торговля женщинами; противодействие торговле людьми; административно-правовое регулирование